2008
DOI: 10.1017/s1463423608000583
|View full text |Cite
|
Sign up to set email alerts
|

A survey of primary and specialised health care provision to prisons in England and Wales

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Some of these factors are clear indicators of the effectiveness of community mental health services. Cornford and colleagues (Cornford, 2007(Cornford, , 2008 found that a third of English and Welsh prisons in 2005 were not able to offer any cognitive behavioral therapy, and that no systems were in place for transfer of medical information on admission or release in more than 70% of prisons. Data from a national US survey from 2002-04 showed that a third of prisoners with diagnoses of schizophrenia and bipolar disorder were not treated with psychiatric drugs (Wilper, 2009).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Some of these factors are clear indicators of the effectiveness of community mental health services. Cornford and colleagues (Cornford, 2007(Cornford, , 2008 found that a third of English and Welsh prisons in 2005 were not able to offer any cognitive behavioral therapy, and that no systems were in place for transfer of medical information on admission or release in more than 70% of prisons. Data from a national US survey from 2002-04 showed that a third of prisoners with diagnoses of schizophrenia and bipolar disorder were not treated with psychiatric drugs (Wilper, 2009).…”
Section: Risk Factorsmentioning
confidence: 99%
“…The provision of healthcare services to prisoners is dependent on the availability of suitably qualified staff, thus any difficulty with recruitment and retention is likely to impact significantly on what is achievable in prisons …”
Section: Introductionmentioning
confidence: 99%
“…Additional challenges, specifically related to inhaler use in this population, include that 65% of young people in custody report leaving school by Year 9, which may impact their health literacy, and the existence of cognitive deficits, including intellectual disability . With regard to the management of patients with asthma in prisons, there is very little published research to guide clinicians . An exception is clinical guidelines for adolescent asthma care, which highlight the need for patient education – including inhaler technique – along with impediments to treating asthma that may occur in the prison environment.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of prisoners are young males who come from a lower socio-economic class. 2 UK prisoners are found to have a higher instance of alcohol and substance dependency, mental illness and are more likely to have been homeless than the rest of the population. 3 Also, as a captive population, they are more susceptible to infectious diseases such as influenza and gastroenteritis, as well as some blood borne viruses like HIV, hepatitis B and C. 3 Following the 'common risk factors approach to health', 4 this poor health status is mirrored in their oral health.…”
mentioning
confidence: 99%